Information System for Incoming and Outgoing Mail Archiving at PT. PLN (PERSERO) Sigli Area, Pidie Regency - Nazariyanti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This study aims to develop an information system for managing incoming and outgoing mail at PT. PLN (PERSERO) Sigli Area, Pidie Regency. The existing manual system, which relied on Microsoft Word and Excel, led to inefficiencies, slow processing times, and the risk of errors in document management. The developed system utilizes Microsoft Visual BASIC 6.0 to automate the archiving, searching, and reporting of mail data, significantly improving operational efficiency. The development process involved several key phases: feasibility study, preliminary planning, system analysis, system design, implementation, and testing. The feasibility study identified the system’s requirements, while the planning phase mapped out the project scope through design tools such as Data Flow Diagrams (DFD). The system analysis phase involved collaboration with users through interviews and surveys, ensuring the design met organizational needs. The system design phase focused on creating the database structure and process flows, while the implementation phase included coding, testing, and user training. The system’s performance was evaluated by comparing its processing speed and data retrieval accuracy to the old manual system. Results indicated a significant improvement in processing time, user satisfaction, and overall efficiency. This new system replaces the outdated manual method, streamlining mail management and enhancing productivity at PT. PLN (PERSERO) Sigli Area